Telomere length is highly heritable and independent of growth rate manipulated by temperature in field crickets. Issue 23 (31st March 2021) - Boonekamp, Jelle; Rodríguez‐Muñoz, Rolando; Hopwood, Paul; Zuidersma, Erica; Mulder, Ellis; Wilson, Alastair; Verhulst, Simon; Tregenza, Tom
Abstract: Many organisms are capable of growing faster than they do. Restrained growth rate has functionally been explained by negative effects on lifespan of accelerated growth. However, the underlying mechanisms remain elusive. Telomere attrition has been proposed as a causal agent and has been mostly studied in endothermic vertebrates. We established that telomeres exist as chromosomal‐ends in a model insect, the field cricket Gryllus campestris, using terminal restriction fragment and Bal 31 methods. Telomeres comprised TTAGGn repeats of 38 kb on average, more than four times longer than the telomeres of human infants. Bal 31 assays confirmed that telomeric repeats were located at the chromosome‐ends. We tested whether rapid growth between day 1, day 65, day 85, and day 125 is achieved at the expense of telomere length by comparing nymphs reared at 23°C with their siblings reared at 28°C, which grew three times faster in the initial 65 days. Surprisingly, neither temperature treatment nor age affected average telomere length. Concomitantly, the broad sense heritability of telomere length was remarkably high at ~100%. Despite high heritability, the evolvability (a mean‐standardized measure of genetic variance) was low relative to that of body mass. We discuss our findings in the context of telomere evolution. Some important features of vertebrate telomere biology are evident in an insect species dating back to the Triassic. The apparent lack of an effect of growth rate on telomere length is puzzling, suggesting strong telomere length maintenance during the growth phase. Whether such maintenance of telomere length is adaptive remains elusive and requires further study investigating the links with fitness in the wild.